Changes in the Nature of Long-Term Fluctuations of Water Flow in the Subarctic Region of Yakutia: A Global Warming Perspective - Raisa Shpakova; Konstantin Kusatov; Sabir Mustafin; Alexander Trifonov (Geosciences, 2019)
Global warming has begun to affect Yakutia, an area recognized as the coldest region of the Northern Hemisphere. Previous research has indicated that the effects of global warming will be long-term. When modeling oncoming climatic changes, researchers often forecast the related water flow changes in various water bodies as well. However, these evaluations frequently differ from the actual water flow data. Thus, the current study identifies and assesses the trends in long-term flow fluctuations in the current context of global warming. This is particularly relevant in the subarctic region of Yakutia, because the local climate is not significantly influenced by anthropogenic factors. The region has an essentially uniform climate, and the river basins within the subarctic zone flow in the same direction. Thus, the study parameters can be adequately compared. Analysis of changes in the water regimen parameters of the rivers in this region is of particular importance. This study demonstrates that the changes in the long-term river regimen in the region, within approximately equivalent climate zones, have been highly and locally variable indifferent areas and time periods. However, we were unable to detect any specific consistency in these changes. The water content of almost all rivers in Yakutia has increased in the last 30 years (approximately), thus confirming general assumptions based on predictive models of climate changes; however, in most cases, such changes were the result of reaching the high-water stage of established long-term cycles. The nature of long-term fluctuations in the water flow of rivers did not change in about half of the Yakutia rivers. One water body showed a further decrease in the water content from the norm, both in terms of duration and water flow rate. Meanwhile, specific water bodies exhibited extreme long-term fluctuations, which are predicted to be a reaction to global warming. Prior to the onset of significant warming in the region, the trends of long-term water discharge ...